A robust array geometry inversion method for a deep-towed multichannel seismic system with a complex seafloor - Li, Jing; Pei, Yanliang; Liu, Chenguang; Zhang, Liancheng; Luo, Xiaohu; Liu, Kai; Li, Weilu (Frontiers in Marine Science, 2023)
Deep-towed multichannel seismic exploration technology has better applicability and more development potential when utilized to invert the geoacoustic properties of deep-sea sediment. The accurate geometric inversion results of the receiving array are crucial for fine submarine sediment imaging and physical property parameter inversion based on deep-towed multichannel seismic data. Thus, this study presents an array geometry inversion method suitable for complex seafloors to address the challenge of precise source-receiver positioning. The objective function of the deep-towed seismic array geometry inversion is built using the shortest path algorithm according to the traveltimes of direct waves and seafloor reflections, and the particle swarm optimization algorithm is used to achieve high-precision inversion of the source-receiver position. The results showed that the proposed method is shown to have incomparable applicability and effectiveness in obtaining exact source-receiver positions for deep-towed multichannel seismic systems. Regardless of the complexity of the seabed morphology, seismic image processing techniques using the source-receiver position data obtained by the suggested method produce fine seismic imaging profiles that clearly and accurately reflect the structural characteristics of sediments. These findings provide insights for the accuracy and reliability of the proposed geometric shape inversion method for deep-towed seismic arrays in practical applications to meet the requirements of near-bottom acoustic detection for fine imaging of deep-sea seabed strata and precise inversion of geoacoustic parameters.